Effect of training focused on executive functions (attention, inhibition, and working memory) in preschoolers exhibiting ADHD symptoms - Re, Anna M.; Capodieci, Agnese; Cornoldi, Cesare (Frontiers in Psychology, 2015)
The development of early intervention strategies for children with symptoms of Attention Deficit Hyperactivity Disorder (ADHD) is important because it provides an opportunity to prevent severe problems in the future. The main purpose of this investigation was to determine the efficacy of a group training for the control of attention, working memory and impulsive behaviors, involving five-year-old children with ADHD symptoms. Twenty-six children with ADHD symptoms and 26 with typical development were randomly divided in two conditions. 13 children in each group were assigned to the training condition and the other to the business as usual condition (normal class activity). Children who participated in the intervention showed an improvement in the tasks measuring their control of attention, impulsive behavior and working memory. Moreover, children with typical development who attended the training also improved their competencies. The results confirm the importance of an early intervention for preschool-age children with ADHD symptoms.